EMPIRICAL RESEARCH OF SOCIAL-PSYCHOLOGICAL FEATURES OF PARENTAL ATTITUDES TO CHILDREN WITH AUTISM - Babatina, Svitlana Ivanivna; Shvestko, Olena Oleksandrivna (Insight: the psychological dimensions of society, 2019)
Purpose. The purpose of the research is to study the socio-psychological characteristics of parental attitudes towards children with autism. The study involved 60 parents of children with autism. Methods. The following methods and research methodologies have been used for achievement the purpose: analysis, systematization and generalization of literary sources, parental attitudes questionnaire PARI (E. Schaeffer, R. Bell), parental attitude test (A. Varga, V. Stolin), questionnaire of emotional relationships in the family (O. Zakharova), "The scale of differential emotions" (K. Izard), the method of determining the dominant state (L. Kulikov). Results. The theoretical overview of the problem has been revealed the essence of the parental attitude as a whole and some features of families raising a child with autism. Empirical research has shown that the main feelings of parents of children with autism are fear and guilt, the most pronounced are the following characteristics of emotional relationships in the family: providing emotional support, the ability to perceive the child’s condition, the prevalent emotional background of interaction. Among parents an excessive concentration on the child prevails; in general, they have a positive or normal attitude towards children. Conclusions. The results suggest that there are direct links between parental attitudes and emotional interaction parameters, dominant states, parental emotions of parents of children with autism. Excessive concentration on the child gives rise to fear and anxiety for the child with autism, feelings of guilt, as well as the emotional background of interaction with child. Unconditional acceptance of the child, the joy of communicating with child, the desire to give emotional support gives rise to parental cooperation with the child. While the parents’ persistent emotional tone influences the child’s adoption, the parents’ fear and anger give rise to the child’s rejection. There is a direct connection between the dominant emotions and the dominant conditions of parents of children with autism. The fears, feelings of guilt and grief felt by the parents of a child with autism and providing emotional support to the child will produce low tone, anxiety, instability of emotional background, helplessness, fatigue, depression.